(3x-5)(x-6)=0

Simple and best practice solution for (3x-5)(x-6)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x-5)(x-6)=0 equation:


Simplifying
(3x + -5)(x + -6) = 0

Reorder the terms:
(-5 + 3x)(x + -6) = 0

Reorder the terms:
(-5 + 3x)(-6 + x) = 0

Multiply (-5 + 3x) * (-6 + x)
(-5(-6 + x) + 3x * (-6 + x)) = 0
((-6 * -5 + x * -5) + 3x * (-6 + x)) = 0
((30 + -5x) + 3x * (-6 + x)) = 0
(30 + -5x + (-6 * 3x + x * 3x)) = 0
(30 + -5x + (-18x + 3x2)) = 0

Combine like terms: -5x + -18x = -23x
(30 + -23x + 3x2) = 0

Solving
30 + -23x + 3x2 = 0

Solving for variable 'x'.

Factor a trinomial.
(5 + -3x)(6 + -1x) = 0

Subproblem 1

Set the factor '(5 + -3x)' equal to zero and attempt to solve: Simplifying 5 + -3x = 0 Solving 5 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -3x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -3x = 0 + -5 -3x = 0 + -5 Combine like terms: 0 + -5 = -5 -3x = -5 Divide each side by '-3'. x = 1.666666667 Simplifying x = 1.666666667

Subproblem 2

Set the factor '(6 + -1x)' equal to zero and attempt to solve: Simplifying 6 + -1x = 0 Solving 6 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -1x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -1x = 0 + -6 -1x = 0 + -6 Combine like terms: 0 + -6 = -6 -1x = -6 Divide each side by '-1'. x = 6 Simplifying x = 6

Solution

x = {1.666666667, 6}

See similar equations:

| 8x=(13x+3) | | (X*40)+(x*1.5*10)=923 | | 8x=13x+3 | | x+x-6=47 | | 4(r=20)=1/5(20r=400) | | 5x-3(2-1x)=1-2x | | 4x^2-3x+7=11 | | 2(a+b)-10= | | x=2y+3w | | 2(AB)-10= | | x^3+6x^2-36=0 | | 2(A*B)=10 | | x^3+6x^2-36=30 | | (2x+2)(5x^2+3x-2)= | | 5+x=x*2.37500 | | 10x^2+-21=0 | | 2x*x^2=6 | | e^5x-9=12 | | 6+12(10-x)=84 | | j-63/2=2 | | 3+(x-2)-3x=3(4x-2) | | -46-(-34)=X/4 | | 7x-4(x-3)=2y | | 5r-6=69 | | x+x-12%=47 | | 3x^2+5x-2x=0 | | 4b-6=8(-8+10b) | | y^3-X^3=91 | | (3a+4)2= | | -14p^2-17p+6= | | (4a-5)(4a+5)= | | 2x-(x+2)+2x-4=12 |

Equations solver categories